Community-Based Approaches to Enhancing Early Childhood Development Quality In Rural Northeastern Thailand: A Critical Ethnographic Study - Wariloon, Achara; Boonsawasdgulchai, Peerapong (Pacific Rim International Journal of Nursing Research, 2025)
Early childhood development is essential for sustained health, economic stability, and social welfare. Despite policy efforts, rural communities in northeastern Thailand continue to experience significant disparities in accessing essential early childhood development resources. Community engagement and the integration of local wisdom have been recognized as pivotal strategies for addressing these gaps and advancing the Sustainable Development Goals. This study examined community-driven approaches to early childhood development in rural Thailand, emphasizing integrated strategies for quality enhancement, enabling conditions, and operational mechanisms. A critical ethnographic methodology was employed, involving a 12-month data collection process that comprised participant and non-participant observations, in-depth interviews, focus group discussions, and document analysis. A purposive sample of 84 participants included caregivers, early childhood educators, healthcare professionals, community leaders, and local officials. Data credibility was ensured through triangulation, and thematic content analysis was applied. The findings demonstrate that sustainable early childhood development in rural Thailand does not arise solely from formal institutional systems but from the dynamic interplay between indigenous knowledge, informal social structures, and locally grounded multisectoral collaboration. The rich findings revealed three key dimensions: 1) an integrated framework for early childhood development improvement, encompassing healthcare access, nutrition, culturally responsive education, and supportive infrastructure; 2) enabling factors such as human resource capacity, data-driven strategies, resource mobilization, and policy alignment; and 3) sustainable governance structures, particularly the “Heet Home Huen Hug” network and “Wong Sole,” an informal community dialogue platform fostering participatory decision-making. These findings inform policies that promote culturally responsive, sustainable, equitable, and inclusive community-based early childhood development.